IL‐6 Secreted from Cancer‐Associated Fibroblasts Mediates Chemoresistance in NSCLC by Increasing Epithelial‐Mesenchymal Transition Signaling. Issue 9 (September 2016) - Shintani, Yasushi; Fujiwara, Ayako; Kimura, Toru; Kawamura, Tomohiro; Funaki, Soichiro; Minami, Masato; Okumura, Meinoshin
ABSTRACT : Introduction: : The tumor microenvironment is composed of different types of stromal cells that represent a key component of tumor progression. Cancer‐associated fibroblasts (CAFs) secrete several factors that promote tumorigenesis. The purpose of this study was to clarify the role of the interleukin‐6 (IL‐6) secreted from CAFs in the communication between CAFs and NSCLC cells that modulates chemoresistance. Methods: : We used standard NSCLC cell lines as well as NSCLC cells, lung normal fibroblasts, and CAFs obtained from specimens from patients with NSCLC to evaluate phenotypic changes. Immunohistochemical analysis was also utilized to examine the stromal changes in tumor specimens obtained from patients with NSCLC who had undergone chemotherapy. Results: : IL‐6 significantly increased transforming growth factor‐β1–induced epithelial‐to‐mesenchymal transition (EMT) changes in cancer cells. Cisplatin treatment increased expression of transforming growth factor‐β in cancer cells, and the conditioned media from cancer cells activated fibroblasts and increased their IL‐6 production. Expression of IL‐6 was increased in CAFs compared with in lung normal fibroblasts. The conditioned media from CAFs induced EMT and resistance to cisplatin in NSCLC cells through IL‐6 signaling. Immunohistochemical analysis showed that stromal IL‐6 expression was correlated with EMT changes in cancer cells as well as with a diffuse distribution of smooth muscle actin–stained fibroblasts. Univariate and multivariate analyses indicated that stromal IL‐6 expression was an independent prognostic factor in patients with NSCLC. Conclusions: : IL‐6 from CAFs enhanced EMT in NSCLC cells. IL‐6 may contribute to maintenance of a paracrine loop that functions as part of the communication between CAFs and NSCLC cells, resulting in chemoresistance.